Pilihan Rasional Indonesia dalam Kebijakan Larangan Ekspor Bijih Nikel - Santoso, Rizal Budi; Moenardy, Dwi Fauziansyah; Muttaqin, Rizqi; Saputera, Denny (Indonesian Perspective, 2023)
Indonesia implemented a nickel ore export ban policy in 2014 with the aim of maintaining sovereignty and control over natural resources, increasing the added value of nickel products, and optimally utilizing nickel wealth to improve people's welfare and strengthen the country's economy. This policy was also taken to strengthen Indonesia's bargaining position in global trade and to show independence and courage in making decisions that could provide long-term benefits for the country. From the perspective of rational choice theory, the nickel ore export ban policy is the result of considering ideological preferences, which focus on efforts to produce nickel derivative products that are processed from upstream to downstream in Indonesia which can then increase the added value of nickel products in the international market which has an impact on creating economic independence from the nickel industry. The nickel ore export ban policy also aims to strengthen Indonesia's bargaining position in international politics and global trade, especially through nickel diplomacy.